Lateral Phase Heterojunction for Perovskite Microoptoelectronics - Li, Lei; Yan, Haoming; Li, Shunde; Xu, Hongyu; Qu, Duo; Hu, An; Ma, Li; Ji, Yongqiang; Zhong, Qixuan; Zhao, Lichen; Xu, Fan; Tu, Yongguang; et al. (Advanced materials (Weinheim), 2024)
Perovskite heterojunction engineering is the prerequisite but still a deficiency in the fabrication of micro‐optoelectronic devices, where the present top‐down or bottom‐up techniques mainly focus on preparing the vertical heterojunction stacks. Perovskite lateral heterojunction structures generally rely on epitaxial growth, which cannot meet the demands of mass production of micro‐devices. Here, a contact diffusion lithography technique is proposed to demonstrate a perovskite lateral phase heterojunction (LPH) polycrystalline film by ion‐driven local phase transition. Under the guidance of thermodynamic simulations, methylamine contact and migration collectively promote in situ formation of α‐phase formamidine‐based perovskite patterns surrounded by δ‐phase polymorphs. Spontaneous type‐I heterojunction alignment between α‐ and δ‐phases establishes energy funnels in the LPH film to facilitate carrier utilization and radiative recombination. The wide‐bandgap δ‐phase also serves as the coplanar isolator to achieve local anti‐leakage for device integration. Based on the bright and stable LPH pattern layer, the near‐infrared microscale perovskite light‐emitting diode (micro‐PeLED) with impressive device performance is achieved by following conventional device fabrication protocol. The proposed LPH enriches the perovskite heterojunction family, creates a new optoelectronic processing platform, and advances its versatile applications in micro‐optoelectronics and photonics. A perovskite lateral phase heterojunction (LPH) polycrystalline film is first demonstrated by a developed contact‐diffusion lithography (CDL) for the fabrication of microscale perovskite light‐emitting diodes (micro‐PeLEDs). Based on the α/δ‐formamidiniumPbI3 (FAPbI3) LPH film with high‐resolution patterns and superior radiative performance, a record‐efficiency near‐infrared micro‐PeLED device is achieved to validate the versatile applications of LPHs in perovskite microoptoelectronics and photonics.